Lithium Ion Wave Function (3Li2+) in a Momentum Chamber at n?3 - Bambang Supriadi; Ega Bonansyah Utoyo; Melisa Putri Febriyanti; Alfiatun Hasanah; Anisa Septi Pratiwi (International Journal Labs, 2023)
Lithium ion (3Li2+) is a light alkali metal which is reactive and flammable when exposed to water or air. Lithium becomes ionic when lithium metal loses two of its three valence electrons. The wave function is a complex quantity that shows the characteristics of the de Broglie wave. The wave function in question is the radial wave function in the particle, because to find the probability that the electron is in the particle, only the radial part of the wave function is needed. However, there is no literature that discusses the wave function in the momentum space in the case of hydrogenic ions. Therefore, this research will examine the wave function of Lithium ion (3Li2+) in the momentum space. This type of research in the preparation of this article uses non-experimental research. Based on the results of the research that has been done, the wave function of Lithium ion (3 Li2+) in the momentum space at n 3 is obtained. The wave function consists of a radial, angular (polar and azimuth) wave function, as well as the wave function of Lithium ion (3Li2+) as a whole. The fundamental difference between the wave function of Lithium ion (3Li2+) in the momentum space and the wave function of hydrogenic atoms in the other momentum space is the value of the radial function caused by the difference in the value of (z) or atomic number.